2012
DOI: 10.2215/cjn.00150112
|View full text |Cite
|
Sign up to set email alerts
|

Differential Outcomes of Expanded-Criteria Donor Renal Allografts According to Recipient Age

Abstract: SummaryBackground and objectives Expanded-criteria donor (ECD) kidneys are used to expand the number of deceased-donor kidney transplants, often for elderly recipients. This study sought to determine whether older recipients had significantly worse outcomes from receiving ECD kidneys and whether outcomes of ECD versus standard-criteria donor (SCD) kidneys differed in younger recipients.Design, setting, participants, & measurements This is a single-center, retrospective review of all primary deceased-donor kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 15 publications
(13 reference statements)
1
23
0
1
Order By: Relevance
“…A total of 135 publications were excluded because the ECD definition was incorrect or lacking, and 82 because of statistical inadequacies in the survival analysis. Thirty‐two publications were finally included in this study . The corresponding main characteristics are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 135 publications were excluded because the ECD definition was incorrect or lacking, and 82 because of statistical inadequacies in the survival analysis. Thirty‐two publications were finally included in this study . The corresponding main characteristics are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of donors, recipients, and transplantations are detailed in Table . Among the 32 publications, 25 (78%) also included SCD kidney recipients . Transplantation periods ranged from 1990 to 2010.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1417 A more recent analysis showed improved long-term patient survival benefits with higher KDPI kidneys (KDPI > 70%) in patients > 50 years old or at centers with median wait times > 33 months. 15 To date, there has been no examination of the long-term survival benefit according to the KDPI > 85% threshold that is now used for allocation or if survival advantages remain when evaluating patients over 60 years old separately.…”
Section: Introductionmentioning
confidence: 99%
“…Mezrich et al [83] have recently reported that elderly patients over 60 years of age with kidneys transplanted from cadaveric marginal donors have a -year shorter patient and graft survival expectancy than that of elderly recipients of standard criteria donors. A similar analysis with 117 patients transplanted from deceased donors indicated a direct correlation between donor age and graft function at 10 years after renal transplantation [84].…”
Section: Cadaveric Marginal Donorsmentioning
confidence: 99%